215k views
0 votes
Solve for b.
r = (b-5)m

User Kim Carlo
by
5.1k points

2 Answers

1 vote

Answer:

See Explanation

Explanation:


r = (b - 5)m \\ \\ (r)/(m) = b - 5 \\ \\ (r)/(m) + 5 = b \\ \\ (r + 5m)/(m) = b \\ \\ \huge \red{ \boxed{b = (r + 5m)/(m) }}

User Kaushal Sachan
by
5.4k points
2 votes

Answer:

b=5m+r/m

Explanation:

Let's solve for b.

r=(b−5)(m)

Step 1: Flip the equation.

bm−5m=r

Step 2: Add 5m to both sides.

bm−5m+5m=r+5m

bm=5m+r

Step 3: Divide both sides by m.

bm/m=5m+r/m

b=5m+r/m

Answer:

b=5m+r/m

User MachineLearner
by
5.2k points